Analisis kandungan unsur hara makro dan karakterisasi jamur dari cairan fermentasi limbah pisang - Hilda Karim; A. Irma Suryani; Yusnaeni Yusuf; Hasriani Hasriani (Seminar Nasional LP2M UNM, 2019)
The use of inorganic fertilizers carried out continuously can damage the physical, chemical and environmental properties, the availability and price of inorganic fertilizers which increase the costs for farmers so that alternative solutions are needed to reduce dependence on the use of inorganic fertilizers and then switch to organic fertilizers. One alternative organic fertilizer that can be used is liquid organic fertilizer from kepok banana waste. The use of organic liquid fertilizer will improve the physical, chemical and biological properties of the soil and contain high organic compounds. The purpose of this study was to determine the macro nutrient content of Kepok banana waste organic fertilizer and to know the morphological characteristics of fungi and their ability to produce IAA hormones from Kepok Banana waste. Based on the results of the analysis of macro nutrient content it is known that the fermentation liquid that produces the best macro elements is CF 30 =, with elemental levels: Nitrogen 0.25%, Phosphorus 2.68%, Potassium 3.24%, Calcium 1.58%, and Magnesium 1.33% and the lowest is CF 15 ≠, with levels of Nitrogen 0.21%, Phosphorus 2.54%, Potassium 2.41%, Calcium 0.84%, and Magnesium 0.54%. The results of this study indicate that in fermentation liquids contain macro nutrients N, P, K, Ca, and Mg that meet the standards set by the government so that they can be used as organic fertilizers. The results of macroscopic and microscopic isolation and fungal characterization showed that the most fungal isolates were found in CF 15 ≠, which were as many as 5 fungal isolates. Whereas for CF 15, 3 mushroom isolates were obtained. And CF 30 ≠ and CF 30 = each 4 fungal isolates.